2019
DOI: 10.21608/adjalexu.2019.57569
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effect of Paclitaxel Loaded on Gold Nanoparticles in Treatment of Induced Oral Squamous Cell Carcinoma

Abstract: INTRODUCTION:Oral squamous cell carcinoma (OSCC) is the sixth most common cancer worldwide with high mortality rate. Conventional treatment strategies have improved but remain far from optimal. Cancer research is focused on improving cancer diagnosis and treatment methods using nanotechnology, by the production and application of nanoscale drug delivery systems. In medicine, several types of nanoparticles have evolved, gold nanoparticle (AuNPs) are an excellent candidate as drug delivery vehicle due to their f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…It was found that the viability of cells decreased in a significant manner at a pH value of 6.5. Meanwhile, Asar et al [134] investigated the effects of AuNPs-paclitaxel on oral squamous cell carcinoma that was induced in Syrian hamsters with those treated with the medicine loaded on AuNPs showing beter results than those treated with rhe drug alone.…”
Section: Paclitaxel (Taxol)mentioning
confidence: 99%
“…It was found that the viability of cells decreased in a significant manner at a pH value of 6.5. Meanwhile, Asar et al [134] investigated the effects of AuNPs-paclitaxel on oral squamous cell carcinoma that was induced in Syrian hamsters with those treated with the medicine loaded on AuNPs showing beter results than those treated with rhe drug alone.…”
Section: Paclitaxel (Taxol)mentioning
confidence: 99%